2012
DOI: 10.1371/journal.pone.0050315
|View full text |Cite
|
Sign up to set email alerts
|

Job Preferences of Nurses and Midwives for Taking Up a Rural Job in Peru: A Discrete Choice Experiment

Abstract: BackgroundRobust evidence on interventions to improve the shortage of health workers in rural areas is needed. We assessed stated factors that would attract short-term contract nurses and midwives to work in a rural area of Peru.Methods and FindingsA discrete choice experiment (DCE) was conducted to evaluate the job preferences of nurses and midwives currently working on a short-term contract in the public sector in Ayacucho, Peru. Job attributes, and their levels, were based on literature review, qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 12 publications
(16 reference statements)
8
29
0
4
Order By: Relevance
“…salary, work hours, prestige, professional development opportunities). Miranda et al [15] and Huicho et al [16] found that in Ayacucho, Peru, physicians were five times more likely, and nurses and midwives 14 times, to choose an urban-based job over a rural one. Incentives that professionals preferred included salary increases and bonus points to gain entry into postgraduate training programmes.…”
Section: Discussionmentioning
confidence: 99%
“…salary, work hours, prestige, professional development opportunities). Miranda et al [15] and Huicho et al [16] found that in Ayacucho, Peru, physicians were five times more likely, and nurses and midwives 14 times, to choose an urban-based job over a rural one. Incentives that professionals preferred included salary increases and bonus points to gain entry into postgraduate training programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Any task-sharing strategy should be implemented alongside other strategies designed to increase the total number of health-care workers. [79][80][81][82] The main obstacle to ensuring that mid-level health workers can help improve health outcomes is that they are often ignored by government policies, health workforce strategies and health system support measures, despite their widespread use. Until these workers are more comprehensively taken into account and supported, their potential contribution will not be fully realized.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The Discrete Choice Experiment (DCE) is a quantitative method used to elicit the value of different preferences that influence job choices (World Health Organization et al ., ). DCE is an increasingly popular methodology as a general preference tool and have been used widely in healthcare setting particularly in valuing health worker preferences (Blaauw et al ., ; Huicho et al ., ; Rockers et al ., ). Determining the appropriate policy to effectively recruit and retain health workers can be informed by data from a DCE.…”
Section: Introductionmentioning
confidence: 97%